Desain Media Pembelajaran “Tata Surya 3D” Berbasis Qreatif Educative dengan Fitur Puzzle dan Kuis Interaktif untuk Siswa Kelas VI Sekolah Dasar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Students often have difficulty understanding the Solar System material given in elementary school science lessons using only conventional methods due to its abstract nature. This study creates and explains the advantages of